Extreme precipitation over Indonesian maritime continent: Uncertainties in satellite estimation and its relationship with low storm top height extreme - Sekaranom, Andung Bayu (2016)
This paper aims to explain the uncertainties in satellite rainfall estimation due to existence of very high near surface rain, but with relatively low cloud top height over Indonesian maritime continent (MC). More than 15 years of satellite precipitation data recorded by tropical rainfall measuring mission (TRMM) were used in this analysis. The result reveals a large discrepancy between the active precipitation radar (PR 2A25) and passive microwave imager (TMI 2A12) over land surface. PR identifies low storm top height associated with large downward increase of radar reflectivity. In contrast, TMI identifies large ice scattering associated with higher storm top height, but with lower rain rates near surface. Further investigation identifies larger relative humidity and upward vertical velocity at middle part of the troposphere for the low storm height extremes. This condition represents a larger condensation around 300-500 hPa level, but less for the upper part. As a result, it produces lower amount of ice at the upper troposphere, contrasting to the type of extreme precipitation identified by TMI.